2016
DOI: 10.1108/ijchm-04-2015-0205
|View full text |Cite
|
Sign up to set email alerts
|

Workplace incivility and its effect upon restaurant frontline service employee emotions and service performance

Abstract: Purpose This study aims to acquire a better understanding about consequences of workplace incivility upon restaurant frontline service employees caused by customers, supervisors and coworkers. The moderating roles of perceived organizational support (POS) and emotion regulation ability (ERA) were also tested to determine the possibility for reducing the negative effect of workplace incivility upon the emotional exhaustion of restaurant frontline service employees. Design/methodology/approach Using data obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
186
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(218 citation statements)
references
References 61 publications
(84 reference statements)
16
186
0
4
Order By: Relevance
“…Scholars (e.g., Hur et al, 2016) revealed a negative relationship between incivility and service employees' creativity, and this link was mediated by emotional exhaustion in South Korean hotels. Cho, Bonn, Han, and Lee (2016) also documented that incivility increases emotional exhaustion, which lowers job service performance of restaurants employees in the United States. Tolerance to incivility was linked with increased workplace withdrawal (Loi et al, 2015), and organizational support has been associated with increased innovation (Ma Prieto & Pilar Perez-Santana, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Scholars (e.g., Hur et al, 2016) revealed a negative relationship between incivility and service employees' creativity, and this link was mediated by emotional exhaustion in South Korean hotels. Cho, Bonn, Han, and Lee (2016) also documented that incivility increases emotional exhaustion, which lowers job service performance of restaurants employees in the United States. Tolerance to incivility was linked with increased workplace withdrawal (Loi et al, 2015), and organizational support has been associated with increased innovation (Ma Prieto & Pilar Perez-Santana, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…First, we advance current knowledge on customer incivility by examining its consequences (i.e., service sabotage). Some scholars have explored the adverse effects of customer incivility on employees in various service industries, such as retail (Kern and Grandey, 2009;Wilson and Holmvall, 2013), department stores (Hur et al, 2015), call centers (van Jaarsveld et al, 2010), banks (Sliter et al, 2010;Sliter et al, 2012), insurance companies (Walker et al, 2014), and restaurants (Cho et al, 2016;Han et al, 2016;Kim and Qu, 2019;Wilson and Holmvall, 2013). However, only a few of them focused on hotel service employees (Hur et al, 2016;Torres et al, 2017).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…First, we apply COR theory to demonstrate that workplace incivility hampers people's propensity to assist coworkers voluntarily, through the influence of reduced positive energy toward and enthusiasm about their job (Penney & Spector, 2005;Welbourne, Gangadharan, & Esparza, 2016). When employees feel frustrated about how they are treated by other organizational members, they may doubt their long-term career prospects with the organization, experience emotional resource drainage, and feel unhappy about their work (Cho, Bonn, Han, & Lee, 2016;Sliter et al, 2012). Such negative feelings in turn may provide employees with an excuse for not undertaking helping activities that could contribute to the success of others but that are not formally required (Foote & Tang, 2008;Lu et al, 2013).…”
Section: Purpose and Hypothesesmentioning
confidence: 99%